EXPLORATION OF VARIATIONS IN POSITIONS OF UPPER AND LOWER INCISORS, OVERJET, OVERBITE, AND IRREGULARITY INDEX IN ORTHODONTIC PATIENTS WITH DISSIMILAR DEPTHS OF CURVE OF SPEE - Kumari, Nita; Fida, Mubassar; Shaikh, Attiya (Journal of Ayub Medical College Abbottabad, 2016)
Background: The position and arrangement of teeth as well as the entire scheme of occlusion differs from one individual to the other .The purpose of this study was to examine differences in position and inclination of incisors, overjet, overbite and lower arch crowding in subjects with different depths of curve of Spee and to determine correlations between depth of curve of Spee and these variables. Methods: The sample comprised of 114 patients (55 females and 59 males) with fully erupted permanent second molars (age 12-25 years), having no history of previous orthodontic treatment, no craniofacial anomalies, and no missing permanent teeth. Study parameters were assessed by using pretreatment lateral cephalograms and dental casts of orthodontic patients. The entire sample was divided into three groups according to depth of curve of Spee (mild Spee=38, moderate Spee=38, severe Spee=38). Descriptive statistics were calculated. Differences between the Spee groups were assessed by analysis of variance. In addition, correlation coefficients were calculated between curve of Spee and other parameters. Results: Statistically significant differences were found in upper incisor inclination (p=0.000), lower incisor inclination (p=0.003), Steiner’s mandibular plane angle (p=0.000), overjet (p=0.001), overbite (p=0.000) and irregularity index (p=0.008) among the Spee groups. Moreover, statistically significant positive correlations were found between curve of Spee and overjet, overbite and irregularity index. Upper and lower incisor inclinations as well as mandibular plane angle were found to have statistically significant but negative correlations with curve of Spee. Conclusion: Overjet and overbite in severe Spee group are larger than in mild and moderate Spee groups. There is negative correlation between curve of Spee depth and inclinations of upper and lower incisors. There is positive correlation between curve of Spee depth and severity of lower anterior crowding and Steiner’s mandibular plane angle. Keywords: Deep bite; Curve of Spee; Irregularity index